Are Anthracycline‐Based Regimens Truly Indicated To Be the Standard Chemotherapy Regimen for Thymic Carcinoma?. Issue 1 (January 2016) - Hirai, Fumihiko; Toyozawa, Ryo; Nosaki, Kaname; Seto, Takashi
ABSTRACT : Introduction : Thymic carcinoma (TC) is an exceptionally rare form of tumor that differs from thymoma by virtue of its very poor prognosis. The difficulties associated with conducting prospective trials involving rare diseases such as TC limit the evidence that can be applied to their treatment. To the extent possible, however, all medical treatment should be evidence based. Methods : We reviewed the clinical results regarding chemotherapy and thymic epithelial malignancies, which include invasive thymoma and TC. We conducted a search of the PubMed database to extract all the chemotherapeutic clinical trials from January 1990 to December 2014. The search included the terms chemotherapy, thymic malignancy, thymoma, and thymic carcinoma and all English‐language publications. Results : From the initial total of 248 articles, we excluded articles that were only in abstract form, review articles, and case reports. In addition, to focus on cytotoxic therapies, we excluded articles on molecular target therapy for TC from our study. After the exclusion criteria were applied, 31 articles remained; they included prospective and retrospective trials. Conclusions : This study assessed the reliable and assessable data on the chemotherapy regimens for TC to identify the evidence‐based recommendations. The results indicate that the only recommended anthracycline‐containing regimen would be carboplatin plus amrubicin—not the combination of cisplatin, doxorubicin, vincristine, and cyclophosphamide—and that the recommended regimens without anthracycline would be carboplatin plus paclitaxel and cisplatin plus docetaxel.